Effect of work on dry matter intake, milk production and reproduction of multipurpose cows fed low quality roughage - Zerbini, E.; Gemeda, T. (China. Ministry of Agriculture, 1993)
The results of the research showed that hay intake was 10 percent greater in working compared to non working cows. Cows responded to underfeeding by a progressive adaptation until a new equilibrium between dietary supply and requirements was reached. However, in draught cows fed low quality roughage, the work-induced increased dry matter intake was not sufficient to cover all energy requirements for work and/or milk. While inadequate feeding may not affect work output, high rates of body weight loss lead to decreased milk production and reproductive ability. Total milk production in a two-year period was similar for working and non working cows. Draught work had a minimal effect on milk production when nutrition was adequate for lactation and work. Roughage diets with less than 8MJ ME/kg DM could not support potential reproductive ability of draught cows. Supplementation improved reproductive performance of working cows and by 365 days post-partum conception rate of non working-supplemented and of working-supplemented cows was similar. However, in working cows, conception was delayed by about 120 days. Body condition at calving significantly affected post-partum reproductive ability of cows. Many more site-specific investigations need to be carried out to find the most economic combinations of feeds through the year and to relate food quality and intake to animal performance, especially in early lactation when the high energy demand for lactation could be associated with work energy needs.